"A Tale of 2 Demons"—Concomitant Presence of Hepatocellular Carcinoma and Primary Neuroendocrine Tumor of Liver: A Case Report and Review of Literatures. (August 2021) - Khanam, Razwana; Pachika, Pranali Santhoshini; Arya, Payam; Bierenbaum, Jason; Kane, Kevin; Saha, Proshikha
Neuroendocrine tumors usually originate from the neuroendocrine cells of gastrointestinal tract and their presence in the liver is mostly in the form of metastases. A primary neuroendocrine tumor in the liver concomitantly with hepatocellular carcinoma is an infrequent phenomenon. We present a 66-year-old woman with a remote history of breast cancer coming with postprandial fullness, later found to have multiple liver masses. After a thorough investigation, she was found to have a combined type of hepatocellular and primary neuroendocrine tumor of liver with pulmonary metastases. She was not a surgical candidate due to distant metastases. She was treated with chemotherapy, immunotherapy, and targeted therapies but continued to deteriorate clinically, and finally succumbed to her illness. The presence of this combined type of tumor in our patient is unique in many different ways: It is extremely rare, she did not have any risk factors for liver cancer, no genetic mutation till date could tie all these cancers (breast cancer, neuroendocrine tumor, and hepatocellular carcinoma) together, and not a lot of literatures/studies performed on this illness.